S. Garfielde, Compiled Laws of the State of California: Containing All the Acts of the Legislature of a Public and General Nature, Now in Force, Passed at the Sessions of 1850-51-52-53, § 127 - (:unkn) unknown (General Publisher, 1853)
Prohibited carrying of pistol, gun, knife, dirk, bludgeon, or other offensive weapon with intent to assault. Punishable by fine of up to $100 or imprisonment for up to 3 months.
--
Keywords: CARRY - INTENT TO COMMIT CRIME